Pengaruh Pembiayaan Bagi Hasil, Dana Pihak Ketiga Dan Beban Operasional Terhadap Tingkat Profitabilitas Perbankan Syariah - Rinda Asytuti; Anisah Santi (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2021)
This study examines the effect of profit-sharing financing, third-party funds, and operating expenses on the level of profitability of Islamic banking with the object of study at PT. BPR Syariah Semarang city in the 2013-2020 period. Sharia Banking is an intermediary financial institution whose role is to collect funds from the wider community. The data collection method in this study is library research using a total sample of 128 samples. The purposive sampling technique carried out the sampling technique. The results showed that profit-sharing financing, third-party funds, and operating expenses had a simultaneous effect on profitability. However, it partially shows that third-party funds and operating expenses have a significant negative effect on the profitability of Islamic banking, especially at PT. BPR Syariah Semarang city registered with OJK for the period 2013-2020.